Relationships between Memory Function, Tau Pathology and Functional Connectivity in the Default Mode Network in Autosomal-Dominant Alzheimers's Disease: A Prelimininary Report (2017)
Background: Disruption of the default-mode network (DMN) has been associated with memory dysfunction and beta-amyloid deposition in preclinical Alzheimer's disease (AD). However, the role of tau accumulation in the integrity of the DMN in AD is not well understood. In this study, we investigated the relationship between DMN integrity, as measured by resting-state functional connectivity, AD pathology (amyloid burden and tau), and memory function in individuals from a Colombian kindred with autosomal-dominant AD, up to fifteen years before the kindred's estimated median age 44 of mild cognitive impairment (MCI). Methods: Twenty-two family members of the Colombian kindred with ADAD due to the Presenilin-1 E280A mutation (8 cognitively-unimpaired carriers, 2 MCI patients, and 12 non-carriers), aged 29–56 years, were included. All participants underwent a comprehensive neuropsychological assessment, PET imaging and resting-state fMRI. Amyloid burden was measured using PiB PET cerebral-to cerebellar DVR, and tau was measured using Flortaucipir (a.k.a AV-1451AV1451) PET cerebral-to-cerebellar SUVR. PET images were analyzed using structural ROIs as defined by Freesurfer. Seed-based functional connectivity analyses of the posterior cingulate cortex and DMN regions were performed. Results: Compared to non-carriers, carriers had elevated levels of cortical β-amyloid (t (20)=-3.78, p=0.004). No statistically significant differences were seen between groups in levels of tau accumulation or DMN functional connectivity. Among mutation carriers, greater DMN functional connectivity was associated with higher mean scores on memory measures (e.g. Logical Memory II: r=0.76, p=0.03), and lower SUVR tau levels in the inferior temporal lobe (r=-0.63, p=0.05). Cortical β-Amyloid was not associated with functional connectivity in the DMN regions (r=-0.61, p=0.06). Conclusions: Preliminary findings support a relationship between disruption of the DMN, memory dysfunction and tau accumulation among carriers of autosomal-dominant AD, years before their estimated clinical onset. Future studies with larger samples are needed to confirm these findings and better understand the relationship between AD pathology and memory networks in preclinical and prodromal AD.